Inter-calibration of a proposed new primary reference standard AA-ETH Zn for zinc isotopic analysis. Issue 2 (22nd November 2016) - Archer, Corey; Andersen, Morten B.; Cloquet, Christophe; Conway, Tim M.; Dong, Shuofei; Ellwood, Michael; Moore, Rebekah; Nelson, Joey; Rehkämper, Mark; Rouxel, Olivier; Samanta, Moneesha; Shin, Ki-Cheol; et al.
Abstract : We have prepared and calibrated a large volume of pure, concentrated and homogenous zinc standard solution. Abstract : We have prepared a large volume of pure, concentrated and homogenous zinc standard solution. This new standard solution is intended to be used as a primary reference standard for the zinc isotope community, and to serve as a replacement for the nearly exhausted current reference standard, the so-called JMC-Lyon Zn. The isotopic composition of this new zinc standard (AA-ETH Zn) has been determined through an inter-laboratory calibration exercise, calibrated against the existing JMC-Lyon standard, as well as the certified Zn reference standard IRMM-3702. The data show that the new standard is isotopically indistinguishable from the IRMM-3702 zinc standard, with a weighted δ 66/64 Zn value of 0.28 ± 0.02‰ relative to JMC-Lyon. We suggest that this new standard be assigned a δ 66/64 Zn value of +0.28‰ for reporting of future Zn isotope data, with the rationale that all existing published Zn isotope data are presented relative to the JMC-Lyon standard. Therefore our proposed presentation allows for a direct comparison with all previously published data, and that are directly traceable to a certified reference standard, IRMM-3702 Zn. This standard will be made freely available to all interested labs through contact with the corresponding author.